A characterization of CMO˙q→ via the commutator of Hardy-type operators on mixed Herz spaces. Issue 16 (2nd November 2022) - Wei, Mingquan
Abstract : In this paper, we introduce and study the mixed central bounded mean oscillation space CMO ˙ q → ( R n ), which is a new central version of the bounded mean oscillation spaces BMO. The pre-dual of CMO ˙ q → ( R n ) is proved to be the mixed Herz–Hardy space HA q → ( R n ) . Moreover, we also give a characterization of CMO ˙ q → ( R n ) via the boundedness of the commutators of n -dimensional Hardy operator and its dual operator on mixed Herz spaces K ˙ q → α, p ( R n ) .